Integration of white rot mushroom cultivation to enhance biogas production from oil palm kernel pulp by solid-state digestion - Panngoen, Pathompong; Leksawasdi, Noppol; Rachtanapun, Pornchai; Chakrabandhu, Yasinee; Jinsiriwanit, Siriwat (Frontiers in Energy Research, 2023)
Solid-state fermentation is one of the promising technologies for biogas production because of its low water footprint and solid output which is potentially used in fuel or agricultural applications. Oil palm kernel pulp (OPKP) is a by-product generated from the extraction of palm kernel oil from the mesocarp of the oil palm tree and usually contains a large amount of lignocellulose and moderate protein content, which makes it suitable for use as a mushroom substrate. Cultivation of white rot mushrooms on lignocellulose may enhance its biodegradation by biodelignification. In this study, the incorporation of the cultivation of edible white rot mushrooms, Pluerotus ostreatus and Pleurotus pulmonarius, to enhance biogas production by solid-state digestion was studied. The biological efficiency of mushroom production from the OPKP substrate of P. ostreatus and P. pulmonarius was 49.81% ± 11.28% and 46.94% ± 13.49%, respectively, corresponding to the substrate weight loss of 15.87% and 13.92%. After 30 days, methane yield obtained through the solid-state digestion of P. ostreatus- and P. pulmonarius-treated OPKP substrates was increased to 98.11 mL/gVS (191%) and 101.10 mL/gVS (197%), respectively, compared with the untreated OPKP substrate. In consideration of energy loss during the biological conversion, the calorific values of the OPKP substrate, P. ostreatus-treated OPKP substrate, and P. pulmonarius-treated OPKP substrate were 11.03 ± 0.71 kJ/g, 9.30 ± 0.23 kJ/g, and 8.83 ± 0.70 kJ/g, respectively, while those of the digestion residues of P. ostreatus and P. pulmonarius-treated OPKP substrates were 8.45 ± 0.13 kJ/g and 8.55 ± 0.11 kJ/g, respectively.